(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The performance and profitability of three commercial broiler strains reared under farming system were investigated in this study. Day-old broiler chicks (n=156) of three different commercial strains (Hubbard classic, Cobb-500 and MPK) were assigned to three treatment groups in a completely randomized block design, each treatment replicated four times, 13 birds per replicate. The birds were reared from d1 to 35 days of age with similar housing, feeding and environmental management condition. Regarding to all parameters collected, live weight and body weight gain were higher (P<0.001) in T2(Cobb-500) group, while the birds of T3 (MPK) group were the lowest. Birds of T1(Hubbard Classic) and T2 (Cobb-500) strain group consumed higher (P<0.001) feeds, while the birds of T3(MPK) had the lowest feed intake. Cobb-500 broiler strain achieved superior (P<0.001) FCR, while the birds of T1 (Hubbard classic) strain group had poorer FCR. Liveability of the broiler strains was unaffected by all the treatment groups. Higher net profit and lower production cost observed in T2(Cobb-500) group than those of other strains, although the difference between the treatment groups was similar. The highly significant measurements of live body weight, weight gain and better FCR values were recorded for Cobb-500 broiler strain, followed by Hubbard classic and MPK, respectively. In conclusion, Cobb-500 broiler strain is appeared to be the most economic to rear amongst the three broiler strains investigated here in response to their performance records. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13931 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 37-43, December, 2011